Novel genes and variants associated with congenital pituitary hormone deficiency in the era of next-generation sequencing - Bando, Hironori; Urai, Shin; Kanie, Keitaro; Sasaki, Yuriko; Yamamoto, Masaaki; Fukuoka, Hidenori; Iguchi, Genzo; Camper, Sally A. (Frontiers in Endocrinology, 2022)
Combined pituitary hormone deficiency (CPHD) is not a rare disorder, with a frequency of approximately 1 case per 4000 live births. However, in most cases, a genetic diagnosis is not available. Furthermore, the diagnosis is challenging because no clear correlation exists between the pituitary hormones affected and the gene(s) responsible for the disorder. Next-generation sequencing (NGS) has recently been widely used to identify novel genes that cause (or putatively cause) CPHD. This review outlines causative genes for CPHD that have been newly reported in recent years. Moreover, novel variants of known CPHD-related genes (POU1F1 and GH1 genes) that contribute to CPHD through unique mechanisms are also discussed in this review. From a clinical perspective, variants in some of the recently identified causative genes result in extra-pituitary phenotypes. Clinical research on the related symptoms and basic research on pituitary formation may help in inferring the causative gene(s) of CPHD. Future NGS analysis of a large number of CPHD cases may reveal new genes related to pituitary development. Clarifying the causative genes of CPHD might rewrite our understanding of the process of pituitary development. We hope that future innovations will lead to the identification of genes responsible for CPHD and pituitary development.